Left hemiparesis due to space-occupying lesion in pregnancy - Luminto; Aryasatiani, Ekarini; Panuntun, Mahendro Aji; Hassan, Bobby Wirawan; Sananta, Tania; Neil, Arya Elbert (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS 1. Present a case report detailing the diagnosis and management of a space-occupying lesion identified late in pregnancy.2. Current studies consistently indicate that the optimal period for tumor removal during pregnancy is the second trimester, balancing maternal and fetal outcomes. This case report contributes to the existing literature by providing a practical reference for managing space-occupying lesions in accordance with the latest evidence.   ABSTRACT Objectives: The objective of this study was to present the findings from cases of space-occupying lesions (SOL) that were diagnosed late in pregnancy. This case report aimed to highlight the importance of considering space-occupying lesions as a differential diagnosis in instances of hemiparesis during pregnancy, thereby raising clinical awareness and improving diagnostic accuracy. Case Report: A female patient aged 30 years 34 weeks pregnant came with complaints of slurred speech since 3 months before entering the hospital accompanied by weakness in the left limbs since 3 months before admission. The patient felt weak and fell in the bathroom 2 times, at the office and at home. The patient had a history of taking aspilet for 1.5 months due to a misdiagnosis as a stroke in a Type B hospital and stopped when she came to the obstetric emergency room at a Type A Hospital for the first time. Cardiothoracograph examination shows a picture of a silent baby. Computed Tomography (CT) Scan examination showed a picture of hydrocephalus. Conclusion: To date, it has not been proven that pregnancy triggers brain tumors. However, increased blood supply to the brain during pregnancy may lead to tumor growth. This is also evident in this case where there is an increase in maternal blood volume and subsequent cerebral blood flow, causing an increase in the size of the SOL. On the other hand, there is no evident that brain tumors directly harm the fetus, though fetal hypoxia may occur indirectly due to maternal respiratory failure.